Defining disease activity states and clinically meaningful improvement in primary Sjögren's syndrome with EULAR primary Sjögren's syndrome disease activity (ESSDAI) and patient-reported indexes (ESSPRI). Issue 2 (5th December 2014) - Seror, Raphaèle; Bootsma, Hendrika; Saraux, Alain; Bowman, Simon J; Theander, Elke; Brun, Johan G; Baron, Gabriel; Le Guern, Véronique; Devauchelle-Pensec, Valérie; Ramos-Casals, Manel; Valim, Valeria; Dörner, Thomas; et al.
Abstract : Objectives: To define disease activity levels, minimal clinically important improvement (MCII) and patient-acceptable symptom state (PASS) with the primary Sjögren's syndrome (SS) disease activity indexes: European League Against Rheumatism (EULAR) SS disease activity index (ESSDAI) and EULAR SS patient-reported index (ESSPRI). Methods: For 790 patients from two large prospective cohorts, ESSDAI, physician evaluation of disease activity, ESSPRI and patients' satisfaction with their current health status were recorded. Receiver operating characteristic curve analyses and anchoring methods were used to estimate disease activity levels of ESSDAI and the PASS of ESSPRI. At follow-up visit, patients and physicians assessed, respectively, whether symptoms and disease activity have improved or not. An anchoring method based on this evaluation was used to estimate MCII of ESSDAI and ESSPRI. Results: Low-activity (ESSDAI<5), moderate-activity (5≤ESSDAI≤13) and high-activity (ESSDAI≥14) levels were defined. MCII of ESSDAI was defined as an improvement of at least three points. The PASS estimate was defined as an ESSPRI<5 points and MCII as a decrease of at least one point or 15%. Conclusions: This study determined disease activity levels, PASS and MCII of ESSDAI and ESSPRI. These results will help designing future clinical trials in SS. For evaluating systemic complications, the proposal is to include patients with moderate activity (ESSDAI≥5) and define response to treatment as an improvement of ESSDAI at least three points. For addressing patient-reported outcomes, inclusion of patients with unsatisfactory symptom state (ESSPRI≥5) and defining response as an improvement of ESSPRI at least one point or 15% seems reasonable.